The Level of Depression, Anxiety, and Stress Among Full-Time Housewives in Selangor, Malaysia - Jest Phia, Dr. Wong; Abdullah Hassan, Rafidah; Fahmi Mohd Teng, Nur Islami (Journal of Science & Technology, 2024)
Physical activity was suggested to improve mental health. However, limited study was done to examine the relationship, especially among housewives. The aim of this study was to determine the relationship between physical activity level with the depression, anxiety, and stress among full-time housewives. A cross-sectional study was conducted among 297 respondents. The respondents were obtained by purposive sampling method. Socio-demographic, DASS-21 and SQUASH questionnaires were administered to the respondents. It was found that 50.5% of respondents were overweight. Level of MET/min of all of the respondents were reported low. The study indicates a high prevalence of housewives who have anxiety (45.1%) followed by stress (39.4%) and depression (34.7%). There is no relationship found between physical activity levels with mental health. As conclusion, effort to reduce sedentary behavior together with improving mental health among housewives is crucial.